The effect of filler loading on the tensile strength of natural rubber compound - Tugau, Juan (2010)
The effects of Carbon Black fillers loading on the Tensile Strength of Natural rubber (SMR) compound were investigated in this study. In this study, 5 KN forces were used to determine Tensile Strength for each ingredient of Rubber compounds are reinforced with filler such carbon black. In general, Natural Rubber (SMR) prepare in range 10 phr, 30 phr and 50 phr of Carbon Black N220 filler loading. The Natural Rubber (SMR) composition also filled with additives such as stearic acid,CBS, zinc white and antioxidant like Aromatic oil meanwhile vulcanization accelerator, and vulcanizing agent like sulphur after 3 hour cool down under room temperature. After 24 hour cooled under room temperature, molding process should be run. After molding, the sample should be cooled under room temperature around 2 days before tensile process. In generally, the amount of the filler added is around 50 parts by weight per 165 parts by weight of the rubber component based on standard ingredient. When the amount of the filler is less by weight, the reinforcing property is insufficient and the wear resistance is poor, while when it exceeds 200 parts by weight, the tensile Strength really strong and the sample become waste because too hard for processing.